Energy management in corn alcohol distilleries in China - Fu Xiaofeng; Tentscher, Wolfgang; Mora, J. A.; Yongping, Zhai; EEC (Bangkok : Asian Institute of Technology, 1992)
The energy consumption pattern in two corn alcohol distilleries in China, Liaoning Province, were investigated and analyzed. The electri city consumption was about 1 MJ e and steam consumption about 18.5 MJth per liter pure alcohol (1 p.a.) in bot h distilleries. Cooking and distillation consumed about 34 % and 56% of the total thermal energy , respectively. This study focused on analyzing the energy conservation potential of a) the vapor recompression cyc l e (VRC) system in distillation processes and b) biogas generated by anaerobic digestion of wastewaters (slops). As already mentioned, the largest energy consumer is distillation wit h a share of 56% (Longguan) and 57% (Shenyang) of the total energy consumption, respectively. A vapor recompression cycle system (heat pump), may reduce the total energy consumption (electricity+ steam) by 44% and 46%. Ass uming an initial investment of 18315$ (Longguan) and 27472$ (Shenyang), payback periods of about 3 and 4 years, respectively could be achieved. By applying the Contois kinetic model, the operating conditions of the existing HYBRID biogas plant were opt imi zed in regard to maximum volumetric me thane production rate (2 . 85 CH4 N m3/m3). The following conditions were proposed: HRT: 1.4 days, temperature: 40°C, substrate con centration: 23.4 CODo/l. If all the s lop (135 m3/d) would be treated, in Longgaun about 1,080 Nm3 CH4/d (about 8 Nm3 CH4/m3 slop) could be generated . This corresponds to 288 MJ/m3 slop at a slop : ethano l ratio of 14.71, to 4.23 MJ/l p.a.. The specific e n ergy consumption may replace 88% of the electricity consumpt ion. Actually, 38% of the slop is treated. Thus, the specific energy production from slop is 1.6 MJ/l p . a .. This could cover , at an energy conversion efficiency of 0.23 from methane to electricity. Only 36% of the electricity consumption could be replaced. And the energy bill will be reduced from 0 . 056 $/1 . p . a to 0.047 $/1 . p.a. (Longquan) and from 0.044 $/1.p.a . to 0 . 038 $/1.p.a. (Shenyang), respectively, calcu l ated with a e l ectricity cost 0.033 $/kWh.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering
Thesis (M.Eng.) - Asian Institute of Technology
Keywords: Distilleries -- Energy concumption